Relating MR relaxation times of ex vivo meniscus to tissue degeneration through comparison with histopathology. Issue 2 (June 2020) - Einarsson, Emma; Svensson, Jonas; Folkesson, Elin; Kestilä, Iida; Tjörnstrand, Jon; Peterson, Pernilla; Finnilä, Mikko A.J.; Hughes, H. Velocity; Turkiewicz, Aleksandra; Saarakkala, Simo; Englund, Martin
Summary: Background: Quantitative magnetic resonance imaging (MRI), e.g. relaxation parameter mapping, may be sensitive to structural and compositional tissue changes, and could potentially be used to non-invasively detect and monitor early meniscus degeneration related to knee osteoarthritis. Objective: To investigate MR relaxation times as potential biomarkers for meniscus degeneration through comparisons with histopathology. Methods: We measured MR relaxation parameters in the posterior horn of 40 menisci (medial and lateral) at a wide range of degenerative stages. T1, T2 and T2 ∗ were mapped using standard and ultrashort echo time sequences at 9.4 T and compared to gold standard histology using Pauli's histopathological scoring system, including assessment of surface integrity, collagen organization, cellularity and Safranin-O staining. Results: All three relaxation times increased with total Pauli score (mean difference per score (95% CI) for T2 ∗ : 0.62 (0.37, 0.86), T2: 0.83 (0.53, 1.1) and T1: 24.7 (16.5, 32.8) ms/score). Clear associations were seen with scores of surface integrity (mean difference per score for T2 ∗ : 3.0 (1.8, 4.2), T2: 4.0 (2.5, 5.5) and T1: 116 (75.6, 156) ms/score) and collagen organization (mean difference between highest and lowest score for T2 ∗ : 5.3 (1.6, 8.9), T2: 6.1 (1.7, 11) and T1: 204 (75.9, 332) ms). The results were less clear for the remaining histopathological measures. Conclusions: MR relaxation times T1, T2 and T2 ∗ of ex vivo human menisci are associated with histologically verified degenerative processes, in particular related to surface integrity and collagen organization. If confirmed in vivo, MR relaxation times may thus be potential biomarkers for meniscus degeneration.